PERILAKU LENTUR BALOK CASTELLATED MODIFIKASI DENGAN PENGAKU TULANGAN DAN KOMPOSIT MORTAR - , Guntara ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Construction using composite IWF steel and concrete have been widely used nowdays, but this construction exists at a high price so the research on composite steel castellated modification beams. This research is done to reduce the prices and also to increase load capacity of composite castellated beams. Results of previous studies showed that an increase in the load capacity of the castellated composite beams with angled stiffeners (Haidar,2014) on castellated composite beams with hexagonal openings (Pribadi,2012) is 31.04%. Failure on the castellated composite with angled stiffeners is at angled stiffener so conducted further research. This study aims to determine the flexural behavior of castellated beams with reinforcement bracing and mortar composite. The tests carried out on one specimen castellated beams are combined with D22 rebar stiffeners and cast with a mortar and given a rectangular hole in the specimen. Mortar mix used was 1: 1.5 with added material viscocrete 10. Methods of testing was done by providing two point static load to determine the flexural behavior of castellated composite beams spaced support 288.6 cm and the distance between the loading is 78.4 cm. The results showed that the load capacity of this study was 178.853 kN increased research on castellated composite hexagonal openings (Pribadi,2012) was 29.83%, and has decreased the castellated composite angled stiffeners (Haidar,2014) was 1.76%. Failure mechanisms that occur are a result of the collapse of bending and stress concentration at the hole (vierendeel mechanism). The pattern of cracks that occur in this research that the tensile cracks in beams and around the holes in the beam. The maximum load capacity of the beam calculated by the Abaqus CAE modeling of 147.351 kN smaller 17.61% of the maximum load capacity beam experiments. Stiffnes beam experiments was larger 16.66% than the beams with hexagonal openings and smaller than of the beams with angled stiffners which 44.99%, while ductility the experiment beam was 6.412 larger than the beams with angled stiffners was 5.280 and smaller than beams with hexagonal openings was 10.578. Keywords: flexible behavior, castellated modification, Abaqus CAE, ductility, stiffness